The Asian Yearbook of Human Rights and Humanitarian Law : Volume 8 - Foster, Steve,; Stanford, Ben,; Vanhullebusch, Matthias, (Human Rights and Humanitarian Law E-Books Online, Collection 2025., 2025)
The Asian Yearbook of Human Rights and Humanitarian Law aims to publish peer-reviewed scholarly articles and reviews as well as significant developments in human rights and humanitarian law. It examines international human rights and humanitarian law with a global reach, though its particular focus is on the Asian region. Volume 8 of the Yearbook covers a wide range of topics focusing on accountability under various legal regimes, which have been organized along four parts: Governance and Accountability, Justice and Accountability, Economic and Social Justice and Violence and Accountability. See Less